Foreign Language Classroom Anxiety, and Enjoyment During Study Abroad: A Review of Selected Paper - Derin, Tatum; Hamuddin, Budianto (Lisan: Jurnal Bahasa dan Linguistik, 2019)
From as simple as speaking up to speaking in public, from finishing a test to studying abroad, anxiety is historically a negative variable affecting many language learners. This paper reviews one of the latest research articles purposively involving anxiety, second language acquisition, and studying abroad written by Dewey, D. P., Belnap, R. K., & Steffen, P. (2018), entitled â€œAnxiety: Stress, Foreign Language Classroom Anxiety, and Enjoyment During Study Abroad in Amman, Jordan.â€ This study conducted in Jordan is a follow up to all the authorsâ€™ project in 2016 with participants who are beneficiaries of a quarter of a century experimentation. This present paper did not adequately funneled its aims but excellently analyzed previous literatureâ€™s and its own research design in a way that the average reader would understand, linking its findings with previous literatureâ€™s findings to give vivid seminal and contemporary context so despite the inconsistent flow. Moreover, this articleâ€™s content is valid (as all references are accurate) and well-argued. Not only is it highly recommended for its innovative anxiety-measure, but also because this research explored three gaps in anxiety and SLA studies: anxiety and L2 development in communicative environment (outside of classroom) abroad, degree of anxiety after receiving interventions to cope with anxiety, and anxiety levels in positive situation (enjoyable classroom). The research found despite levels of classroom enjoyment increasing, learners still show physiological signs of increased anxiety levels, more so if they have the tendency toward anxiety and low proficiency score prior to SA. Therefore this paper seen anxiety as a physiological conditions on â€œworry about an eventâ€ (p. 2), which makes this study believes that anxiety in language education context is an emotional state in which learnersâ€™ feel negative about their knowledge and skill in their language performance.